The Clarion of Syria A Patriot's Call against the Civil War of 1860 - Al-Bustani, Butrus (University of California Press, 2019)
When Nafir Suriyya-"The Clarion of Syria"-was penned between September 1860 and April 1861, its author Butrus al-Bustani, a major figure in the modern Arabic Renaissance, had witnessed his homeland undergo unprecedented violence in what many today consider Lebanon's first civil war. Written during Ottoman and European investigations into the causes and culprits of the atrocities, The Clarion of Syria is both a commentary on the politics of state intervention and social upheaval and a set of visions for the future of Syrian society in the wake of conflict. This translation makes a key historical document accessible for the first time to an English audience. Rereading this work in the context of today's political violence in war-torn Syria and elsewhere in the Arab world helps us gain a critical and historical perspective on sectarianism, class rebellion, foreign invasions, conflict resolution, Western interventionism, and nationalist tropes of reconciliation. "The first English translation of this foundational text offered alongside a fantastic historical introduction, this is an excellent and much-needed contribution from uniquely qualified scholars." STEPHEN SHEEHI, author of The Arab Imago BUTRUS AL-BUSTANI was a nineteenth century Ottoman Arab educator and public intellectual regarded by many as the first Syrian nationalist owing to the publication of his Nafir Suriyya following the 1860 communal disturbances in Mt. Lebanon and Damascus. JENS HANSSEN is Associate Professor of Arab Civilization, Middle Eastern, and Mediterranean History at the University of Toronto. He is author of Fin de Siècle Beirut and coeditor of Arabic Thought beyond the Liberal Age and Arabic Thought against the Authoritarian Age. HICHAM SAFIEDDINE is Assistant Professor of History of the Modern Middle East at King's College, London. He is author of Banking on the State: The Financial Foundations of Lebanon, cofounder of Al-Akhbar English, and editor of The Legal Agenda English Edition.